Analisis Perkembangan Fisik-Motorik Tercapai pada Usia Dasar di MIN 2 Sleman Yogyakarta - Rahmawati, Ely; Maulinisa, Rizki; Suyadi, Suyadi (Al-Riwayah : Jurnal Kependidikan, 2019)
This article departs from Hurlock volume 1 edition 6, stating that children who have a proportion of fat and heavy bodies have a high level of intelligence. However, the facts on the ground found that some children who had thin and long bones had good intelligence and motor power compared to other students. The subjects in this study had good fine motor skills and gross motor skills. The child has the skills to connect the dots correctly. This ability is in line with its ability to mix and match the color of the image, then adjust one image to another in the sticking activity, neat cutting ability. In this case it is influenced by the good factor of parenting and does not put pressure on the education process. In line with that, the nutrition received by children is well regulated and maintained in order to get nutritious food intake, and is also influenced by the school environment and in the community that supports the child's development process.